McArdle's Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Muscle biopsy specimens from 48 patients with biochemically proven phosphorylase deficiency (McArdle's disease) have been analyzed by gel electrophoreis (SCS-PAGE), immunoblotting, and immunotitration (ELISA) at Columbia University College of Physicians and Surgeons, New York, NY.